CAN YOU HEAR MY VOICE?: ANALYSIS OF STUDENTS EXPERIENCE FROM A SEMESTER OF SUDDEN ONLINE LEARNING - Fadzlin Ahmadon; Hajar Izzati Mohd Ghazalli; Hazlifah Mohd Rusli (Journal of Islamic, Social, Economics and Development, 2022)
Much like their peers in many universities around the world, students of UniversitiTeknologi MARA (UiTM) experienced their first full-time implementation of online learningduring the 2020 government-mandated lockdown. An attempt was made to understand thepreparedness and concerns of students prior to the carrying out of online learning in UiTM.Analysis of the questionnaire disclosed students’ concerns on their ability to understand andfocus with classes and a fear of technical failures. After the semester ended, anotherquestionnaire was issued to the same set of students with more questions exploring theiropinions, preferences and experience. Review of answers discovered aspects of online learningliked and disliked by students, and also factors that most negatively impacted their onlinelearning experience. Additionally, a further investigation on responses of students thatanswered both questionnaires showed some of them changed their minds on several aspectsafter experiencing online learning. This discloses a possibility of further acceptance of theonline learning system when students’ fears and issues are properly addressed in the future.